UTILIZATION OF LEARNING MANAGEMENT SYSTEM (LMS) ON INDEPENDENT LEARNING PLATFORM (PMM) FOR TEACHERS - Oto Nurfalah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT This study aims to explore the use of Learning Management System (LMS) in the Merdeka Mengajar Program (PMM) for Teacher Leaders Batch 11. LMS as a digital tool that supports distance learning and teacher professional development is expected to improve the quality of learning and accelerate educational transformation in Indonesia. Through a qualitative approach, this study identifies how LMS is used in the implementation of PMM, as well as the benefits obtained by teacher leaders in developing their teaching competencies and practices. The results of the study indicate that LMS provides ease in accessing learning materials, improves collaboration between teachers, and enables more effective learning evaluation. In addition, LMS also helps teacher leaders in strengthening technological skills, which are very relevant to the needs of 21st century education. Overall, the use of LMS in PMM has a positive impact on teacher professional development and the implementation of the Merdeka Belajar principle which is more flexible and based on student needs. This study concludes that LMS is an effective tool in supporting the objectives of PMM, namely improving teacher competency and improving the quality of learning in schools. Keywords: LMS, Platform, Teachers